Production of aflatoxins by Aspergillus flavus and of fumonisins by Fusarium species isolated from Brazilian sorghum - Silva,Josefa B. da (2004)
Fifty-nine Aspergillus flavus and 35 Fusarium verticillioides strains, isolated from freshly harvested (10) and stored (130) Brazilian sorghum samples, were tested regarding their ability to produce aflatoxins (coconut milk agar) and fumonisins (rice culture), respectively. Aflatoxins B1 and B2 were detected by TLC, and fumonisins B1 and B2 were analyzed by HPLC. Thirty-eight (64.4%) A. flavus strains produced detectable levels of aflatoxins at concentrations ranging from 12.00 to 3282.50 µg/kg (AFB1 + AFB2), while thirty two (91%) F. verticillioides strains produced FB1 at concentrations ranging from 0.12 to 5.38 µg/g. Two F. proliferatum strains produced low fumonisin levels. The toxigenic potential of A. flavus (64.4%) and F. verticillioides (91.5%) strains observed in sorghum samples indicates that rigorous control should be directed at the storage conditions of these products to minimize contamination with toxigenic deteriorating fungi, preventing further hazard to human and animal health.